Electric vehicles trucks – overview of technology and research selected vehicle - Łebkowski, A. (Scientific Journal of Gdynia Maritime University, 2017)
The article describes the technological solutions applied in electric trucks, especially in the IVECO DAILY 50C ELECTRIC truck. The basic vehicle parameters and properties are presented. The results of the truck’s electric powertrain testing in road conditions and on roller dyno are introduced. The comparison of the examined design with other technological solutions is performed and discussed.